Immediate and Persistent Effects of Temperature on Oxygen Consumption and Thermal Tolerance in Embryos and Larvae of the Baja California Chorus Frog, Pseudacris hypochondriaca - Mueller, Casey A.; Bucsky, Julie; Korito, Lindsey; Manzanares, Samantha (Frontiers in Physiology, 2019)
The developmental environment has significant immediate effects on phenotypes, but it may also persistently or permanently shape phenotypes across life history. This study examined how developmental temperature influenced embryonic and larval phenotypes of Baja California chorus frog (Pseudacris hypochondriaca), an abundant amphibian in southern California and northern Baja California. We collected egg clutches from native ponds in northern San Diego County within 24 h of fertilization, and clutches were separated and distributed between constant temperatures of 10, 15, 20 and 25°C for incubation. Oxygen consumption rate (V̇O2), developmental stage, and embryo and yolk masses were measured throughout development. Time to 50% hatch, survival at 50% hatch, and hatch duration were determined. Development rate was strongly affected by temperature, with warmer temperatures reducing time to hatch and hatch duration. Survival to hatch was high across all temperatures, > 90%. Mass-specific V̇O2 of embryos either remained constant or increased throughout development, and by hatching energy demand was significantly increased at higher temperatures. There were limited temperature effects on growth, with embryo and yolk dry mass similar between temperatures throughout embryonic development. To examine long-term effects of embryonic temperature, we reared hatchlings from each temperature until onset of larval feeding. Once feeding, larvae were acclimated to 20 or 25°C (>2 weeks). Following acclimation to 20 or 25°C, we measured larval mass-specific V̇O2 and critical thermal maximum (CTMax) at a common developmental stage (Gosner stages 32 – 36, “hindlimb toe differentiation”). Embryonic temperature had persistent effects on larval V̇O2 and CTMax, with warmer temperatures generally resulting in similar or higher V̇O2 and CTMax. This partially supported a ‘warmer is better’ effect of embryonic incubation temperature. These results suggest that in a thermally robust amphibian species, temperature may program the phenotype during early development to construct traits in thermal tolerance and energy use that may persist. Overall, P. hypochondriaca displays a thermally robust phenotype, and it is possible that amphibians that possess a wider range of phenotypic plasticity will be relatively more successful mitigating effects of climate change.